Factors affecting university image among graduate alumni: A case study of Qatar university. Issue 6 (June 2022) - Haza, Khalifa A.; Abdel-Salam, Abdel-Salam G.; Mollazehi, Mohammad D.; Mohamed, Radwa Ismail; Hasan, Mahmood A.; Al-Tameemi, Rusol A.; Bensaid, Ahmed; Johnson, Chithira; Romanowski, Michael H.
Abstract: Various factors influence the students' perception of universities and university image. This study explores five factors affecting university image among Graduate Alumni. Surveys, administered to 597 graduate alumni were assessed to determine Graduate Alumni perspectives toward their university. Findings revealed that the key factors that impacted graduate alumni affecting the university's image and reputation were gender, nationality, level of study, and the ability of the institution to equip graduates with certain specific skills. Based on these findings, the university should consider further examining these areas to provide a more in-depth understanding of how these factors work to shape graduate students' perspectives of the university and develop ways to address areas that need to be developed and improved. Abstract : University image; Postgraduate students; Reputation.